Perencanaan Tempat Pengolahan Sampah 3R (Reduce Reuse Recycle) di Kecamatan Kesamben Kabupaten Jombang - Nanda Henik Pratiwi; Yayok Suryo Purnomo; Tuhu Agung Rachmanto; Naniek Ratni Juliardi A.R (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2022)
The increase in the amount of waste coupled with the lack of waste management facilities, as well as the lack of knowledge and public awareness in managing waste causes the accumulation of waste to have an impact on environmental pollution. In the Kesamben sub-district, Jombang, there is no waste management facility, so people choose to do open burning, throw garbage on the side of the road, and even throw garbage directly into the river. From these problems, a TPS 3R was planned in Kesamben District. In planning the TPS 3R, population data and population projections, waste generation data, waste composition, waste generation projections and local area HSPK are required. Data collection on waste generation and composition was carried out by sampling at residents' homes. The results of the sampling obtained the weight of waste generation of 0.1393 kg/person/day with a waste volume of 0.0022 m3/person/day. The composition of the waste consists of organic waste, plastic, paper, cloth/textile, glass, Styrofoam, and diapers. With the percentage of waste composition, respectively, namely 64.55%; 19.7%; 8.49%; 1.71%; 0.41%; 0.75%; and 4.38%. From this data, a TPS 3R building is planned which can process waste up to a volume of 164.55 m3/day. Consists of a reception room, sorting room, inorganic waste storage room, plastic waste processing unit, organic waste processing unit, liquid organic fertilizer storage room, residual waste storage room, and supporting facilities. From the planning that has been done, it takes a budget plan of Rp2.052.524.176,35.